Bonding Strength Regulates Anchoring‐Based Self‐Assembly Monolayers for Efficient and Stable Perovskite Solar Cells. (20th June 2021) - Li, Erpeng; Liu, Cong; Lin, Hongzhen; Xu, Xiaojia; Liu, Shuaijun; Zhang, Shuo; Yu, Miaojie; Cao, Xiao‐Ming; Wu, Yongzhen; Zhu, Wei‐Hong
Abstract: Anchoring‐based self‐assembly (ASA) has emerged as a material‐saving and highly scalable strategy to fabricate charge‐transporting monolayers for perovskite solar cells (PSCs). However, the interfacial hole‐extraction and electron‐blocking performances are highly dependent on the compactness of the ASA monolayers, which has been largely ignored though it is very crucial to the efficiency and stability of PSCs. Here, strategically designed hole‐transporting molecules with different anchoring groups are incorporated to investigate the effect of bonding strength on monolayer quality and correlate these with the performance of p‐i‐n structured PSCs. It is unraveled that the anchoring groups with a stronger bonding strength are advantageous for improving the assembly rate, density, and compactness of ASA monolayer, thus enhancing charge collection and suppressing interfacial recombination. The prototypical PSCs based on optimal ASA monolayer achieve a high power conversion efficiency (PCE) of 21.43% (0.09 cm 2 ). More encouragingly, when enlarging the device area by tenfold, a comparable PCE of 20.09% (1.0 cm 2 ) can be obtained, suggesting that the ASA strategy is practically useful for scaling‐up. The robust anchoring of the ASA monolayer also enhances devices stability, retaining 90% of initial PCE after three months. This study provides important insights into the ASA charge‐transporting monolayers for efficient and stable PSCs. Abstract : Molecular hole‐transporting materials with different anchoring groups are synthesized. The anchoring groups with a stronger bonding strength enable greatly enhanced compactness of self‐assembly monolayer, which benefits hole‐extraction and electron‐blocking in complete devices. When applied in inverted perovskite solar cells, 1 cm 2 devices show a promising power conversion efficiency of over 20% with high stability.